Expression effective communication of da'wah for Muhammadiyah young women on social media - Somae, Erik Tauvani; Nuryana, Zalik (International Journal of Communication and Society, 2024)
Rahma (Rahma.id) is an Islamic website formed by a group of young Muhammadiyah women as a literacy medium with a moderate thought narrative. The purpose of this study is to analyze the literacy expression of young Muhammadiyah women in the Rahma network in the midst of social media expansion. This study uses a qualitative method with editors and contributor writers as respondents and uses the critical discourse studies paradigm of Teun A. van Dijk. The results of this study indicate that: (1) The phenomenon of the emergence of Rahma in the midst of social media expansion is an expression of young Muhammadiyah women to actualize gender equality in the contestation of Islamic discourse; (2) Rahma is a forum for young Muhammadiyah women who try to exist culturally and create social relations amidst the diversity of Islamic, Indonesian, and humanitarian narratives on social media; (3) Young Muhammadiyah women in the Rahma network read the current effective and balanced da'wah opportunities through digital literacy. (4) Although based on the young women's literacy movement in Muhammadiyah, Rahma is open, accommodating, and not limited to gender, age, organization, even religion as long as it is in line with Muhammadiyah's moderate Islamic mission.